Hospitalizations in pediatric patients with immune thrombocytopenia in the United States. (3rd July 2016) - Tarantino, Michael D.; Danese, Mark; Klaassen, Robert J.; Duryea, Jennifer; Eisen, Melissa; Bussel, James
Abstract: To examine utilization and outcomes in pediatric immune thrombocytopenia (ITP) hospitalizations, we used ICD-9 code 287.31 to identify hospitalizations in patients with ITP in the 2009 HCUP KID, an all-payer sample of pediatric hospitalizations from US community hospitals. Diagnosis and procedure codes were used to estimate rates of ITP-related procedures, comorbidity prevalence, costs, length of stay (LOS), and mortality. In 2009, there were an estimated 4499 hospitalizations in children aged 6 months–17 years with ITP; 43% in children aged 1–5 years; and 47% with emergency department encounters. The mean hospitalization cost was $5398, mean LOS 2.0 days, with 0.3% mortality ( n = 13). With any bleeding (15.2%, including gastrointestinal 2.0%, hematuria 1.3%, intracranial hemorrhage [ICH] 0.6%), mean hospitalization cost was $7215, LOS 2.5 days, with 1.5% mortality. For ICH (0.6%, n = 27), mean cost was $40 209, LOS 8.5 days, with 21% mortality. With infections (14%, including upper respiratory 5.2%, viral 4.9%, bacterial 1.9%), the mean cost was $6928, LOS 2.9 days, with 0.9% mortality. Septic shock was reported in 0.3% of discharges. Utilization included immunoglobulin administration (37%) and splenectomies (2.3%). Factors associated with higher costs included age >6 years, ICH, hematuria, transfusion, splenectomy, and bone marrow diagnostics ( p < 0.05). In conclusion, of the 4499 hospitalizations with ITP, mortality rates of 1.5%, 21%, and 0.9% were seen with any bleeding, ICH, and infection, respectively. Higher costs were associated with clinically significant bleeding and procedures. Future analyses may reveal effects of the implementation of more recent ITP guidelines and use of additional treatments.